USING MODERN TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Sidiqova N.N; Latipova Marjona (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
At present the foreign languages taught in many institutions of higher education have various computer-based programs and technologies developed by the language industry and now they are available to teachers and students. The fast growing of foreign language field represents a major challenge to teachers and students and in particular to educators in charge of curricula planning.